Ethical problematics and political corruption in Indonesian elections: A review of dignified justice theory - Fajrin, Yaris Adhial; Ishwara, Ade Sathya Sanathana (Trigin Publisher, 2024)
The purpose of this research is to discuss political corruption associated with ethical problems that are factually new in the 2024 elections in Indonesia. The practice of political corruption in the 2024 elections can be said to be massive, referring to the symptoms of new totalitarianism, namely the engineering of legal and democratic mechanisms to accommodate the political interests of certain parties. Viewed from the perspective of dignified justice, in holding the 2024 elections, there are attempts to degrade and castrate the implementation and enforcement of legal norms and ethical norms at the same time. The phenomenon of money politics, the politicization of social assistance, and the engineering of legal and democratic mechanisms through the weakening of judicial institutions, in this case the Constitutional Court (MK), is proof that there is weak enforcement of legal norms and ethical norms in the 2024 elections. Therefore, the main solution to minimize political corruption is to simultaneously understand, implement, and enforce legal norms and ethical norms as the main substance of a dignified justice perspective. Meanwhile, a concrete solution to prevent or overcome political corruption during the election period is to ensure a clear separation of powers and independence in law enforcement.